Kualitas Fisik Daging Ayam Kampung Jowo Super (Joper) Yang Diberi Tepung Serai Wangi (Cymbopogon Nardus L.) Dalam Ransum: Physical Quality Of Jowo Super Native Chicken (Joper) Meats With Given Citronella Meal (Cymbopogon Nardus L.) In The Ration - Handarini, MP., Dr. Ir. Ristika; Wahyuni, S.Pt., M.Si., Dewi; Satya, Pandu Tri (Jurnal Peternakan Nusantara, 2024)
Jowo super chickens, or joper chickens, result from a cross between male native chickens and laying hens. Joper chickens can produce good meat and a faster growth rate than ordinary native chickens.The physical quality of meat from jowo super native chickens (joper) given citronella meal (Cymbopogon nardus L.) in the ration is the focus of this research, which aims to provide relevant information to the public and interested parties. This research was carried out from July to September 2023 using a Completely Randomized Design (CRD) method with five treatments and four replications. The treatment given is feeding with the following composition: R0: basic ration; R1: basic ration + 2% citronella meal; R2: basic ration + citronella meal 4%; R3: basic ration + 6% citronella meal; R4: basic ration + 8% citronella meal. This study measured pH, water holding capacity (WHC), cooking loss, and tenderness. The results of the study showed that the provision of citronella meal in the ration did not have a significant difference (P>0.05) on pH, water holding capacity (WHC), cooking loss, and tenderness of Joper chicken meat. The conclusion of this study is the addition of citronella meal in the ration has not been able to improve the physical quality of joper chicken meat.